APPLICATION OF DEMONSTRATION METHOD ON PRAYER MATERIAL FOR GRADE 3 SD NEGERI 040486 GURUKINAYAN - Lulu Diah Lestari (Journal of Quality Islamic Education Research, 2024)
The purpose of this study was to analyze the importance of implementing the demonstration method in learning Islamic Religious Education (PAI) on prayer material for grade 3 of SD Negeri 040486 Gurukinayan. This research method is a qualitative type of Phenomenology. The subjects of the study were teachers, students, and the principal. The object of this study was the application of the demonstration method in learning PAI on prayer material for grade 3 of SD Negeri 040486 Gurukinayan. The results of the study were that the application of the demonstration method was very well applied in prayer material lessons. The use of the demonstration method in teacher learning is required to directly demonstrate the prayer movement material to students so that they can accept and follow what the teacher demonstrates properly and correctly. The use of the demonstration method is important to apply in learning PAI on prayer material because students' attention can be more focused on following learning activities, the learning process learned by students is more focused